2008
DOI: 10.1002/app.29233
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial electrospun chitosan/poly(vinyl alcohol) nanofibers containing silver nitrate and titanium dioxide

Abstract: Chitosan/poly(vinyl alcohol) (PVA) nanofibers with antibacterial activity were prepared by the electrospinning of a chitosan/PVA solution with a small amount of silver nitrate (AgNO 3 ) and titanium dioxide (TiO 2 ). Nanofibers with diameters of 270-360 nm were obtained. The yield of low-viscosity chitosan (LCS)/PVA nanofibers was higher than that of high-viscosity chitosan (HCS)/PVA, and the water content of the HCS/PVA nanofibers and the LCS/PVA nanofibers were 430 and 390%, respectively. The nanofibers deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
59
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(60 citation statements)
references
References 19 publications
1
59
0
Order By: Relevance
“…Thus, many researchers observed that the decrease of fiber diameters when electrospinning voltages increased (36,37). Similarly, we observed that attenuated ruptures of the charged jet at lower voltages were advantageous for fabricating micron-size microspheres.…”
Section: Resultssupporting
confidence: 68%
“…Thus, many researchers observed that the decrease of fiber diameters when electrospinning voltages increased (36,37). Similarly, we observed that attenuated ruptures of the charged jet at lower voltages were advantageous for fabricating micron-size microspheres.…”
Section: Resultssupporting
confidence: 68%
“…Other nanofibers electrospun of blends of chitosan and inorganic nanoparticles are not discussed in detail here, such as titanium dioxide (TiO 2 ) nanoparticles/chitosan/PVA electrosun nanofibers exhibiting antibacterial activities against Staphylococcus aureus and Escherichia coli [99], palladium nanoparticles/chitosan grafting acrylic copolymer (PdNPs/ CS-g-AA) blend electrospun nanofibrous catalyst applied to catalyze alpha-octene hydrogenation in normal temperature and pressure [100], etc. The combination of the characteristics of the inorganic nanoparticles and the features of chitosan nanofibers could lead to more products with unique properties that can fit special needs.…”
Section: Electrospinning Of Blends Of Chitosan and Inorganic Nanopartmentioning
confidence: 99%
“…the coaxial electrospinning provides a versatile method to encapsulate immobilized antibacterial agents in the core-shell micro/nanofibers. The antibacterial mechanism of this new kind of core-shell nanofibers may be different from the mechanism of Ag-doped antibacterial nanofibers [22,23]. One reason is that the PySMPU like PUPy53 and PUPyMDI35 contains large fraction of BINA unit which have an amido group in !…”
Section: Characterizationmentioning
confidence: 93%